Peningkatan Kapasitas Pemasaran Produk Pertanian Berbasis Digital Di Kabupaten Tasikmalaya - Akbar, Akhmad Hidayat Nurul; Makarim, Siti Amirah; Haryati, Sani (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
This community service activity aims to improve digital-based agricultural product marketing capacity for farmer groups in Tasikmalaya Regency. The main problems faced by partner farmers are limited market access, lack of knowledge about digital marketing, and insufficient ability to utilize agricultural e-commerce platforms. The methods used include extension, practical training, and intensive mentoring for four months. The target was 45 farmers from three villages, namely Hegarwangi Village (Bantarkalong District), Wangunsari Village (Bantarkalong District), and Girijaya Village (Bojongasih District). The results showed a significant increase in participants' knowledge of digital marketing (average pretest score 42.3 increased to 78.6 on posttest), and an increase in the number of farmers who successfully utilized digital platforms for product marketing by 68%. Average farmer income increased by 32% during the mentoring period. This activity is recommended to be expanded to other villages in Tasikmalaya Regency.